Drácula, um vampiro vitoriano: o discurso moderno no romance de Bram Stoker - Rodrigues, Andrezza Christina Ferreira (2008)
This work intends to do an analysis of some discourses historically constituted by modernity progress, during the last decades of XIX century, having as reflections main point Bram Stoker s novel Dracula, first published in 1897. Surrounding Stoker s novel, it is possible to glimpse the cultural lines of successful scientism allied health knowledge, especially concerned to blood. At 1880s social Darwinism opened through a biological cover hereditary degeneration theory to English people, reinforcing the sanitary idea developed by Chadwick, which has had its expression through illness control and degeneration by blood connections. The medical theories see blood as gemmules word adopted by Darwin himself to mean granule which has influence on body and mind because of hereditary presence made by ancestors, for example been a worker, been insane, develop promiscuous behavior or became a beggar. In that moment English people has been concerned about this themes, which had been debated by Galton who began the idea of good race for British society